2008
DOI: 10.1016/j.genm.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and the diabetic kidney

Abstract: Background-Across all ages, the incidence and rate of progression of most nondiabetic renal diseases are markedly higher in men compared with age-matched women. These observations suggest that female sex may be renoprotective. In the setting of diabetes, however, this female protection against the development and progression of renal disease is diminished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 84 publications
3
62
1
5
Order By: Relevance
“…Several experimental studies have demonstrated a renoprotective role of exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [36][37][38][39]. However, an experimental model of type 1 diabetes has also, however, shown that relative balance, rather than the absolute levels of sex hormones, correlates with conditions associated with diabetic complications [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have demonstrated a renoprotective role of exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [36][37][38][39]. However, an experimental model of type 1 diabetes has also, however, shown that relative balance, rather than the absolute levels of sex hormones, correlates with conditions associated with diabetic complications [40].…”
Section: Discussionmentioning
confidence: 99%
“…2 The loss of female "protection" in diabetes remains controversial. 3,4 Moreover, some risk factors for DN differ between men and women, 5 suggesting sex-specific mechanisms that may be related to differences in the hormonal profiles as estrogen exerts renoprotective effects in nondiabetic persons. 4 Furthermore, women with T1D have lower estradiol concentrations and a hormonal profile that more closely resembles that of men.…”
mentioning
confidence: 99%
“…4 Furthermore, women with T1D have lower estradiol concentrations and a hormonal profile that more closely resembles that of men. 3 Nevertheless, the role of estrogen in the progression of DN still remains ambiguous. 6 DN clusters in families, and the sibling risk ratio is conspicuously high for ESRD, suggesting that genetic variation influences the risk of ESRD.…”
mentioning
confidence: 99%
“…The influence of estrogens on the development and progression of diabetic kidney damage, although a subject of intense translational research effort, remains a matter of controversy [1][2][3][4][5]. The aim of this review will be to summarize the clinical and experimental data regarding the effects of estrogens on the development and progression of diabetes-induced kidney damage, with special regards to the most recent data concerning podocyte injury and dysfunction.…”
mentioning
confidence: 99%
“…The uncertainty of the contribution of gender to the progression of renal disease is even greater when we consider diabetes-induced kidney damage, in the setting of either type 1 or type 2 diabetes [2,3]. Several clinical studies indicate that diabetic kidney damage progresses faster in males than in females [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%